2013
DOI: 10.1186/1746-1596-8-94
|View full text |Cite
|
Sign up to set email alerts
|

An extraordinary T/NK lymphoma, nasal type, occurring primarily in the prostate gland with unusual CD30 positivity: case report and review of the literature

Abstract: Extranodal NK/T cell lymphoma(NKTCL), nasal type, occurring primarily in the prostate gland, is extremely rare. We present a case of primarily prostatic NKTCL in a 59-year-old man suffering from dysuria. Histological examinations revealed that diffused, large-sized, pleomorphic lymphocytes were arranged in an angiocentric distribution with large areas of geographic necroses. Additionally, the prostatic glands were diffusely infiltrated by heteromorphous lymphocytes forming lymphoepithelial lesions. The tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Hemophagocytosis is observed in up to 3% of cases 36,46–63 and hydroa vacciniforme-like lymphoproliferative disorder (HVLL), an indolent lymphoproliferative disorder of EBV+ NK-cells or γ/δ T-cells can precede ENKTL-NT by several years. 64 There is no evidence of HVLL preceding ENKTL-NT in U.S. or European ENKTL-NT.…”
Section: Clinical Presentation Of Enktl-nt In Different Ethnic Groupsmentioning
confidence: 99%
“…Hemophagocytosis is observed in up to 3% of cases 36,46–63 and hydroa vacciniforme-like lymphoproliferative disorder (HVLL), an indolent lymphoproliferative disorder of EBV+ NK-cells or γ/δ T-cells can precede ENKTL-NT by several years. 64 There is no evidence of HVLL preceding ENKTL-NT in U.S. or European ENKTL-NT.…”
Section: Clinical Presentation Of Enktl-nt In Different Ethnic Groupsmentioning
confidence: 99%
“…This expression rate is higher than the 30% in the WHO book of ENKTL . In de novo ENKTL, large cell morphology usually correlates with CD30 expression; and in some studies, a poorer prognosis . In this current study, the lymphoma cells of effusion ENKTL are usually large and anaplastic, which is distinct from de novo ENKTL.…”
Section: Discussionmentioning
confidence: 45%
“…10 Radiologic studies showed no evidence of lymphadenop- In de novo ENKTL, large cell morphology usually correlates with CD30 expression; and in some studies, a poorer prognosis. [35][36][37] In this current study, the lymphoma cells of effusion ENKTL are usually large and anaplastic, which is distinct from de novo ENKTL. We recommend that CD30 immunostaining be performed for all effusion ENKTL cases; and target therapy with brentuximab vedotin, an anti-CD30 antibody-drug conjugate, might be considered a therapeutic option for those with CD30-expressing tumors.…”
Section: Discussionmentioning
confidence: 78%
“…Extranodal NK/T-cell lymphomas characteristically involve the upper aerodigestive tract, with the nasal cavity being the prototypic site [3]. Rarely, the tumour occurs in prostate, adrenal glands and lung [4][5][6]. According the WHO criterion, the neoplastic lymphoid cells usually co-express NK cell markers such as CD56 and T cellassociated antigens like CD3, CD2 with expression of cytotoxic markers such as TIA-1, Perforin and Granzyme-B [6].…”
Section: Discussionmentioning
confidence: 99%